Gender-specific Rhabdomyolysis risk in Alzheimer’s disease patients receiving memantine: a pharmacovigilance study - Tabassum, Nadira (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.